2D and 3D Classification Systems for Adolescent Idiopathic Scoliosis: Clinical Implications and Technological Advances - Wenqing Wei; Liang Cheng; Yating Dong; Tianyuan Zhang; Yaolong Deng; Jiale Gong; Fang Xie; Junlin Yang (Orthopaedic Surgery)
ABSTRACT Classification systems for Adolescent Idiopathic Scoliosis (AIS) play an important role in guiding both surgical planning and conservative treatments. Traditional 2D classification systems, such as the Lenke, King and Lehnert‐Schroth classifications, have been widely used for the clinical diagnosis and treatment of scoliosis. However, with the growing understanding of the three‐dimensional nature of scoliosis and advancements in 3D reconstruction technologies, 3D classification systems are gaining increasing attention. This paper reviews the current applications, advantages, and limitations of different 2D and 3D classification systems, focusing on their clinical significance in treatment planning. While 3D classification systems offer clear advantages in capturing the complexity of spinal deformities, their clinical implementation faces challenges such as high costs and technical complexity. Additionally, studies show that computer‐assisted technologies, artificial intelligence can significantly improve the accuracy and consistency of classification systems, reducing human errors. The paper also explores the future directions of classification system development, emphasizing the potential of combining 2D and 3D technologies and the impact of these advancements on personalized scoliosis treatment.